Genome‐wide association identifies candidate genes for drought tolerance in coast redwood and giant sequoia. (8th December 2021) - De La Torre, Amanda R.; Sekhwal, Manoj K.; Puiu, Daniela; Salzberg, Steven L.; Scott, Alison D.; Allen, Brian; Neale, David B.; Chin, Alana R. O.; Buckley, Thomas N.
SUMMARY: Drought is a major limitation for survival and growth in plants. With more frequent and severe drought episodes occurring due to climate change, it is imperative to understand the genomic and physiological basis of drought tolerance to be able to predict how species will respond in the future. In this study, univariate and multitrait multivariate genome‐wide association study methods were used to identify candidate genes in two iconic and ecosystem‐dominating species of the western USA, coast redwood and giant sequoia, using 10 drought‐related physiological and anatomical traits and genome‐wide sequence‐capture single nucleotide polymorphisms. Population‐level phenotypic variation was found in carbon isotope discrimination, osmotic pressure at full turgor, xylem hydraulic diameter, and total area of transporting fibers in both species. Our study identified new 78 new marker × trait associations in coast redwood and six in giant sequoia, with genes involved in a range of metabolic, stress, and signaling pathways, among other functions. This study contributes to a better understanding of the genomic basis of drought tolerance in long‐generation conifers and helps guide current and future conservation efforts in the species. Significance Statement: Climate change brings more frequent and severe drought events that challenge the survival of natural populations of plants. While most of our knowledge about drought tolerance comes from annual and domesticated plants, the genomic basis of drought tolerance in long‐generation trees is poorly understood. Here, we aim to fill this gap by identifying candidate genes in two conifer species, coast redwood and giant sequoia.